Fatal pulmonary embolism following compression sclerotherapy for varicose veins. Issue 573 (July 1973) - McMaster, P.; Everett, W. G.
Abstract : A case of fatal pulmonary embolism following compression sclerotherapy treatment of varicose veins is reported. This is the first death following this form of treatment recorded.